THE CLINICAL CASE OF THYMECTOMY USING COMBINED APPROACHES - I. I. Dzidzava; I. V. Dmitrochenko; E. E. Fufaev; B. N. Kotiv; O. V. Barinov; D. A. Yasyuchenya; S. N. Bardakov; V. A. Popov; P. N. Zubarev; V. V. Kovalenko (Вестник хирургии имени И.И. Грекова)
Various surgical approaches was proposed to remove the thymus. At the same time, the choice of surgical approach in each patient should have been differential. We presented the clinical case of the removal of thymus tumor using combined (subxyphoid and transthoracic) surgical approach.The authors declare no conflict of interest.The authors confirm that they respect the rights of the people participated in the study, including obtaining informed consent when it is necessary, and the rules of treatment of animals when they are used in the study. Author Guidelines contains the detailed information.